2020
DOI: 10.1101/2020.06.15.153924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An integrated gene catalog of the zebrafish gut microbiome reveals significant homology with mammalian microbiomes

Abstract: 24Gut microbiome research increasingly utilizes zebrafish (Danio rerio) given their amenability to 25 high-throughput experimental designs. However, the utility of zebrafish for discerning 26 translationally relevant host-microbiome interactions is constrained by a paucity of knowledge 27 about the biological functions that zebrafish gut microbiota can execute, how these functions 28 associate with zebrafish physiology, and the degree of homology between the genes encoded by 29 the zebrafish and human gut micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…Through metagenomic analysis, we discovered that bacteria found in the gill samples of zebrafish with NP-induced injury, such as the phyla Proteobacteria, Bacteroidetes, and Actinobacteria, accounted for more than 95% of the total bacteria count; these types of bacteria are all found in normal zebrafish gut microflora [52][53][54][55]. This result is likely attributable to the fact that the zebrafish in the experiment were kept under pathogen-free conditions; no pathogens other than normal flora were present.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Through metagenomic analysis, we discovered that bacteria found in the gill samples of zebrafish with NP-induced injury, such as the phyla Proteobacteria, Bacteroidetes, and Actinobacteria, accounted for more than 95% of the total bacteria count; these types of bacteria are all found in normal zebrafish gut microflora [52][53][54][55]. This result is likely attributable to the fact that the zebrafish in the experiment were kept under pathogen-free conditions; no pathogens other than normal flora were present.…”
Section: Discussionmentioning
confidence: 94%
“…The relative abundance (% relative to the total) of the bacteria populations was analyzed in specific hypervariable regions of 16S ribosomal RNA through new-generation sequencing analyses (Fig 4 and S2 Fig in S1 Data). We found that the phyla Proteobacteria, Bacteroidetes, and Actinobacteria, all of which are bacteria found in normal zebrafish gut microbiomes [52][53][54][55], accounted for more than 95% of the total bacteria counts (Fig 4). Because the fish culture conditions did not include pathogens, these results indicate that TiO 2 NP-induced zebrafish gill injury is associated with opportunistic infection of the gut normal flora.…”
Section: Tio 2 Np-induced Mortality In Zebrafish Is Associated With Increased Gill Bacterial Countsmentioning
confidence: 95%
“…Indeed, host gut microbiota interactions [ 124 ] and neurological disorders [ 125 , 126 ] that mirror human conditions have been independently investigated using zebrafish. However, the combined efforts of the characterization of recently developed zebrafish disease models for ASD and AD, the establishment of microbial approaches including GF culture [ 127 , 128 ] and metagenomic analyses of the microbiota [ 129 , 130 ], and the expansion of their neurobehavioral repertoires [ 131 , 132 , 133 , 134 ] may allow dissection of the signaling pathways for the host–bacteria interactions in neurological disorders, discussed in the following sections. The key advantages of the zebrafish model for studying the MGBA are summarized in Figure 2 .…”
Section: Zebrafish As a Model System For Mgba Studiesmentioning
confidence: 99%
“…Although the exact taxonomies of the microbial communities in humans, mice, and zebrafish differ, there is a trend towards interspecies conservation at the phylum level [ 187 , 188 ]. In addition, host responses to gut colonization by microbiota have been reported to be significantly shared between zebrafish and mouse models [ 189 ], and zebrafish, mouse, and human microbiomes are known to have similar abundances of functional pathways (i.e., DEG pathways) [ 130 ] which suggests that functional and mechanistic findings using the zebrafish microbiota may have direct translational implications for understanding human microbiota functions.…”
Section: Zebrafish As a Model System For Mgba Studiesmentioning
confidence: 99%
“…9 Previous genomic investigation has identified the presence of butyrate metabolic genes in the zebrafish gut metagenome; however, the key bacterial enzyme for butyrate synthesis butyryl coenzyme A (CoA):acetate-CoA transferase has not been specifically detected. 9,10 Acetate, butyrate, and propionate have been measured in several species of teleosts. [11][12][13][14][15] We have used conservation between mammalian intestinal function and immunity to create zebrafish models of human intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%